The Symposium of the 5,000 - Sick, David H. (The journal of theological studies, 2015)
Starting from the use of the Greek word symposion in the Gospel of Mark (6:39), this article reads the feeding of the 5,000 as a public distribution of food, a well-known means of euergetism in the Greco-Roman world. Following recent work by Pauline Schmitt Pantel, Katherine Dunbabin, and John Donahue, we note the expansion of the classic symposium to include these public distributions in the Hellenistic and Roman periods. The large commensal gatherings often offered a menu similar to that of Jesus’ feast. The fish are intended as a complement or topping for the bread and mark the meal with a certain refinement. Wine, a common element of the Greco-Roman distributions, is not mentioned in the synoptic gospels but is implied by the account in the Gospel of John through its connection to the seder. The menus for the Greco-Roman distributions can be recovered from epigraphic commemorations of the events, and these inscriptions share a few stylistic elements with the account in Mark. Mark intends his audience to compare Jesus’ public feast with the celebration for Herod’s birthday, which precedes it in the text.